Comparative Study of Intramedullary Flexible Nailing and External Fixator Result in the Management of Fractures Tibial Shaft. (Gustilo type II, type IIIA, and type IIIB) - Susheel Kumar Soni; Sunil Patidar; Manish Bajaj; Vaibhav Mandovera (Journal of Orthopaedic Case Reports)
Introduction: Open tibial fractures, usually caused by high-energy trauma, are among the most common long-bone fractures. Clinically, the treatment of open tibial fractures remains a major therapeutic problem for surgeons because of the poor soft-tissue coverage and blood supply in the tibia, with resultant difficulties arising from infection and poor bone healing. In this study, we will assess the results of intramedullary flexible nailing and external fixators in the management of fractures shaft tibia (G.A. type II, IIIA, and IIIB). Materials and Methods: Twenty-six patients who presented with open fractures of the tibial shaft type II, IIIA, and IIIB (Gustilo) were treated. We included patients of both sexes, aged between 18 and 65 years with diaphysial fractures 5 cm distal to the tibial tuberosity and at least 5 cm proximal to the tibial plafond, irrespective of fibula fracture. Thirteen patients were treated by external fixator and 13 patients by flexible intramedullary nailing and the outcomes were assessed. Results: The mean age in our study was 36 years for the flexible intramedullary nailing group and 38 years for the external fixator group. Male involvement was 69.23% (18 patients) and female involvement was 30.76% (eight patients). In the present study, for external fixation mean age was 38 years (25–60), the union rate was 84.4%, the non-union rate was 16.6%, and the malunion was 33.3%, Pin track infection rate was 50%, the average time of union 27.08 weeks (26–30 weeks) and osteomyelitis is 16.6%. In the present study results for flexible intramedullary nailing, the mean age is 36 years (20–62 years), mal-union is 8.3%, pain at nail head rate is 16.6%, the average time of union is 25 weeks, and union achieved in all cases. Conclusion: Flexible intramedullary nailing is more efficacious than external fixators in the management of fractured shaft tibia (Gustilo type II, IIIA, and IIIB). The advantages observed are maintaining limb alignment and fewer serious complications, fewer operations needed, and a better range of motion of adjacent joints obtained. It reduces the hospital stay of patients and later patients can return early to work, thus minimizing psychological trauma and financial burden. Flexible intramedullary nailing has an easy learning curve. The external fixator group had more disability and difficulties in daily routine activities such as sleeping, bathing, and other social activities.